2005
DOI: 10.1038/sj.onc.1208995
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of KrasD12 knockdown on tumorigenesis: increased immune-mediated tumor clearance and abrogation of tumor malignancy

Abstract: Activating mutations in the human KRAS proto-oncogene are acquired during the earliest stages of colorectal cancer development. If mutant KRAS is to be used as a target for therapy in colorectal cancer, tumor growth should depend on its continued presence. Here, we report that stable knockdown of Kras D12 in murine C26 colorectal cancer cells by RNA interference resulted in loss of transformed properties in vitro. The incidence of subcutaneous tumor formation was reduced by 60% and the lag time was increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 17 publications
7
37
1
2
Order By: Relevance
“…The RAS family plays an important regulatory role in the processes of cell growth and differentiation, with KRAS acting as a molecular switch and participating in a number of cancer pathways such as that of colorectal cancer [48][49][50]. Studies have shown that 40-50% of human colorectal cancer is caused by the activity of KRAS protein expression, and inhibition of KRAS expression can inhibit tumor growth [51][52][53]. In recent years, a hypothesis that adherent A/E E. coli has a connection with colorectal carcinogenesis in humans has been put forth [54][55][56].…”
Section: Espf May Induce Colitis and Colorectal Carcinogenesis Through mentioning
confidence: 99%
“…The RAS family plays an important regulatory role in the processes of cell growth and differentiation, with KRAS acting as a molecular switch and participating in a number of cancer pathways such as that of colorectal cancer [48][49][50]. Studies have shown that 40-50% of human colorectal cancer is caused by the activity of KRAS protein expression, and inhibition of KRAS expression can inhibit tumor growth [51][52][53]. In recent years, a hypothesis that adherent A/E E. coli has a connection with colorectal carcinogenesis in humans has been put forth [54][55][56].…”
Section: Espf May Induce Colitis and Colorectal Carcinogenesis Through mentioning
confidence: 99%
“…Directly following resection, the specimens were taken to the pathology department where a part of the tumor was excised for experimentation. The biopsy was mechanically dissociated using scalpels and vigorous trituration to yield small fragments (o1 mm 3 ) and single cells. In some cases, where indicated, the tissue fragments were incubated with thermolysin (0.05% in 10 mM Hepes pH 7.2, 37 1C, 1 h).…”
Section: Tumor Samplesmentioning
confidence: 99%
“…Recent evidence suggests that the sustained presence of oncogenic KRAS is required for maintenance of the transformed and malignant properties of several types of tumor cells. [1][2][3] This makes KRAS, or KRAS-activated signaling intermediates, attractive targets for therapeutic intervention. Reovirus T3D is an oncolytic virus that kills susceptible cells by inducing apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…C26 is an aggressive colorectal cancer cell line that contains constitutively activated Kras due to an activating point mutation in codon 12 (G12D) (22). The Nras and Hras genes in this cell line do not contain activating mutations.…”
mentioning
confidence: 99%
“…As a control, we established cell lines transduced with the empty lentivirus pLL3.7 vector (C26-pLL). Efficient and specific knockdown of Kras was demonstrated by Western blot analysis for Kras and, as control, Nras (22). These cell lines were used to analyze the effect of Kras on C26 sensitivity to reovirus-induced oncolysis.…”
mentioning
confidence: 99%